Development of an Enzyme-Aided Pre-Treatment Process for Production of Pumpkin (Cucurbita Moschata L.) Powder - Shavakhi, Forough (2011)
Pumpkin powder is one of the main products of pumpkin which can be easily stored and conveniently used in processed food. Spray drying is a highly appropriate process for heat-sensitive products and has been widely used in many fruits and vegetables. Appropriate feed viscosity and solids concentration are necessary to easily pump the feed into a spray dryer and obtaining an acceptable yield. On the other hand, the main problem in the spray drying of fruits and vegetables is stickiness and a part of this problem can be solved by addition of maltodextrin which offsets spray drying performance due to increasing viscosity. The inclusion of an enzymatic maceration step in fruits and vegetables processing leads to decreasing the viscosity. Therefore, the main objective of this research was to develop a process for production of spray-dried pumpkin powder using enzyme as a pre-drying treatment. The aim of the first experiment of this study was the maceration of raw pumpkin flesh in order to prepare a spray drying feed with an appropriate color, aroma, viscosity, and low molecular weight sugars. Therefore, the effects of different enzymes (pectinase, cellulase and amylase) on maceration or liquefaction of pumpkin were investigated in order to select the best treatment for preparation of the base feed for spray drying. Based on the results on aroma (Principal Component Analysis of zNose data), color, viscosity and sugar analysis, the best treatment to macerate pumpkin and produce a suitable base feed for spray drying was using 2.5% v/w Pectinex® Ultra SP-L (Novozymes, Denmark). The viscosity value of macerated pumpkin with Pectinex® Ultra SP-L, 2.5 % v/w (0.102 Pa.s) was increased after addition of maltodextrin. To get more reduction in feed viscosity, Celluclast® 1.5 L (Novozymes, Denmark) was added to Pectinex-treated pumpkin. Therefore, the next set of experiments was conducted to optimize the effects of three variables namely Celluclast concentration (0-1% v/w, x1), maltodextrin (MD) concentration (15–30% w/w, x2) and spray dryer inlet temperature (150-190°C, x3) on pumpkin powder characteristics using pumpkin macerated with 2.5% v/w Pectinex® Ultra SP-L as the base feed. The results indicated that the response surface models were significantly (p≤0.05) fitted for response variables of process yield, moisture content, water activity and hygroscopicity. The overall optimum region that would result in desirable powder characteristics was predicted to be obtained by a combined air inlet temperature of 180°C, Celluclast concentration of 0.7 % (v/w) and MD concentration of 23% w/w. Furthermore, the results showed that the glass transition temperature (Tg) of pumpkin powder increased with an increase in air inlet temperature and MD concentration. Also, the Tg of pumpkin powder was found to increase with increasing of concentration of Celluclast up to 0.5% v/w. Conversely, increasing the concentration of Celluclast above 0.5% v/w (and up to 1% v/w), decreased the Tg of the pumpkin powder. Surface morphology images of powder captured by scanning electron microscopy (SEM) confirmed the results. In addition, the effects of the three variables mentioned above on reconstitution of pumpkin powder based on color, water solubility index (WSI) and water absorption index (WAI) were described. The results revealed that a second order polynomial regression model was fitted to all response variables studied except for a-value in powder and reconstituted powder, reconstituted hue-value and also ΔE and WSI with good determination coefficients (R2>80%). Total color change (ΔE) of initial pumpkin puree and reconstituted pumpkin powder solution varied from 16.08 to 20.04. Solubility index of the pumpkin powder increased as a result of adding MD and increasing the air inlet temperature. Water absorption index of pumpkin powder in this study varied from 66.0 to 140.48, indicating that powders was able to hold water at a maximum of 1.4 times their weight. Therefore, it is not suitable as a thickening ingredient. In the next stage, the effects of two anti-caking agents namely tri-calcium phosphate (TCP) and calcium silicate (CS) at 0, 0.1, 0.2 g of each/100g puree on pumpkin powder characteristics before and after storage for 8 weeks in ambient condition were investigated. Anti-caking agents showed positive effect on the cyclone recovery in spray drying of pumpkin powder and could improve the recovery of spray-dried pumpkin powder. Powder containing anti-caking agents showed higher Tg during 8 weeks of storage indicating that these additives acted as successful anti-caking agents. Finally, rheological characteristics of enzymaticaly-macerated pumpkin and also spray dried reconstituted powder were evaluated to determine the potential application of pumpkin powder. Results revealed that the enzymatically-macerated pumpkin exhibited a yield stress and shear stress–shear rate data was best fit to Herschel-Bulkley Model at any given temperature with R>0.94, while shear stress–shear rate data of reconstituted powder solutions were fitted to Power Law Model without definite yield stress. Consistency coefficients (K) of enzymatically-macerated pumpkin was decreased at 25ºC (4.44 Pa.sn) to 55ºC (3.41 Pa.sn) followed by an increase at 65ºC (4.78 Pa.sn) and afterward. Rheologically, the reconstituted powder behaved similarly to fruit juice. Flow activation energy of consistency index and apparent viscosity were 7.37 and 7.53 kJ/mol respectively. Based on rheological properties of reconstituted powder solution, one of the potential applications of spray-dried pumpkin powder is its suitability for preparation of pumpkin juice. The finding of this research revealed that Pectinex® Ultra SP-L in different concentrations (2.5, 3.5, 4.5 and 5.5% v/w) and incubation times (2.5, 2, 1.5 and 1 h, respectively) was able to macerate pumpkin. The optimum concentration of 2.5% v/w was used for preparation of base feed for spray drying since it is more economical. Celluclast® 1.5 L was able to decrease the feed viscosity and increase the recovery of pumpkin powder. The best anti-caking agent was tri-calcium phosphate, based on a study on storage for 8 weeks. Results obtained showed that the pumpkin powder prepared in this study was not suitable as a thickening ingredient but can be used in the preparation of pumpkin juice.